We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
122
1
avatar

What is (f*g)(x)? 

F(x)=x^4-9

g(x)=x^3+9

 

(f*g)(x)=?

 Mar 15, 2019
 #1
avatar+105454 
0

(f * g) (x)  means

 

f(x) * g(x)  =

 

[ x^4 - 9 ] [ x^3 + 9 ] =

 

x^4 * x^3 - 9*x^3 + 9*x^4  -9*9 =

 

x^7 + 9x^4 - 9x^3 - 81

 

 

cool cool cool

 Mar 15, 2019

19 Online Users